The international drugs trade - Arnold, Guy (Routledge, 2005)
"An introduction to the complex topic of the international drugs trade, this book touches upon the key players - countries, individuals, cartels, agencies, etc. - as well as the key laws and policies affecting drug trafficking and policing, consumption and distribution. The International Drugs Trade is broadly informative and comparative, examining drug movements by geographical region, drugs by their type and their effects, and national and international laws and policies." "Providing a comprehensive account of one of the world's most powerful industries, The International Drugs Trade is an essential resource for students and scholars of politics, international relations, and public policy."--Jacket